Development of e-module based on problem-based learning on human respiratory organs for grade V UPT SDN 11 Tiumang, Dharmasraya District - Elsa Rahmawati; Zaka Hadikusuma Ramadhan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aims to develop an E-Module based on problem-based learning using material related to the Human Respiratory System. This study uses quantitative and qualitative methods. This study is a development research project (Research and Development) utilising the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). To test the validity of the E-Module product based on problem-based learning (PBL) development, it requires two media experts, two language experts, and two design experts. The results of the study indicate that the validation process of the e-module based on Problem-Based Learning, using material on human respiration, to improve students' creative thinking skills yielded